2006
DOI: 10.1055/s-0037-1622150
|View full text |Cite
|
Sign up to set email alerts
|

Healing venous ulcers with different modalities of leg compression

Abstract: Summary Background: Compression therapy (CT) is the stronghold of treatment of venous leg ulcers. We evaluated 5 modalities of CT in a prospective open pilot study using a unique trial design. Patients and methods: A group of experienced phlebologists assigned 31 consecutive patients with 35 venous ulcers (present for 2 to 24 months with no prior CT) to 5 different modalities of leg compression, 7 ulcers to each group. The challenge was to match the modality of CT with the features of the ulcer in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…At present there is a wide variation in the management of venous leg ulcers. In USA, Unna's boots (a noncompliant, plaster-type bandage) are often applied in many crural ulcer patients; in UK, multilayer elastic compression is widely used, while in mainland Europe and Australia, the inelastic, short stretch bandaging is commonly prescribed [3, 17, 18]. According to the recent clinical evidence analysis published in 2011 in the venous ulcer healing, compression bandages and stockings cure more ulcers compared with no compression, but there is still very little evidence-supported data answering the question: which bandaging technique is most effective [4]?…”
Section: Discussionmentioning
confidence: 99%
“…At present there is a wide variation in the management of venous leg ulcers. In USA, Unna's boots (a noncompliant, plaster-type bandage) are often applied in many crural ulcer patients; in UK, multilayer elastic compression is widely used, while in mainland Europe and Australia, the inelastic, short stretch bandaging is commonly prescribed [3, 17, 18]. According to the recent clinical evidence analysis published in 2011 in the venous ulcer healing, compression bandages and stockings cure more ulcers compared with no compression, but there is still very little evidence-supported data answering the question: which bandaging technique is most effective [4]?…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis was performed on the basis of a recent pilot study of our group, 13 where the effect size w (͌ (X 2 /N) was 0.39 regarding healing. This revealed the necessity to include 52 ulcers to ascertain a difference between the two groups with a power of 0.8 at a two-sided P Ͻ .05.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical notion was generated from data of a non-randomized pilot study that had shown an advantage of low-strength medical compression stockings (MCS) over bandages. 13 Furthermore, the latest randomized trials reported a higher rate of healing with elastic graduated stockings as compared with bandages and a possible advantage when the stockings were removed at night. 14,15 In view of the various potential benefits of low-strength MCS, we performed the present prospective randomized open-label trial.…”
mentioning
confidence: 98%
“…Further studies suggested that ulcers treated with stockings providing lower pressures healed faster than those treated with high-pressure bandages. 21,22 The antithetical findings call for more studies to evaluate their use on a wider scale.…”
Section: Compression For the Treatment Of Venous Ulcerationsmentioning
confidence: 99%